Examination of the Lawmaking Power of the Executive Arm of Government, Separation of Powers, Checks and Balances under the Nigerian Constitutional Democracy - Esu, Effiong A. (ABUAD Law Journal, 2023)
Modern day government is designed to reduce concentration of power, promote personal liberty and prevent abuse of power. Many Constitutions are therefore crafted to provide for distribution of governmental powers, separation of powers, checks and balances. This is a notable feature of the 1999 Constitution of Nigeria which has prescribed the scope and limits for each arm of government, and areas to integrate the dispersed power into a workable government. Recently, the Supreme Court of Nigeria in Attorney-General of Abia State & 35 ors v. Attorney General of the Federation nullified Executive Order 10 issued by the President of the Federal Republic of Nigeria which sought to grant financial autonomy to the state judiciary and legislature. The judgment of the apex Court has raised a number of constitutional issues which are germane to our constitutional democracy. It has brought to the fore the need for each organ to be independent within its own domain and no one organ of government has supervisory power or control over other arms. It espoused the sanctity of the doctrine of separation of powers, checks and balances as desirable under the Nigerian Presidential Constitution. The confusion associated with the advent of executive orders requires urgent clarification not only for the citizens but the operators of the constitution. This paper adopts the doctrinal research methodology and critically analyzes the constitutional provisions on the law-making power of the executive arm, separation of powers, and draws experiences from advanced constitutional democracies. It concludes that the 1999 constitution recognizes some level of integration and interaction amongst the different arms of government, and maintains a delicate balance to avoid concentration of power. It is therefore the responsibility of each arm of government to operate within its area of competence and respect the limit prescribed by the constitution.